Charged kaon femtoscopic correlations in pp collisions at √s=7 TeV - Abelev, Betty; Angelov, Venelin; Busch, Oliver; Fasel, Markus; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Klein, Jochen; Krawutschke, Tobias; Kweon, MinJung; Lohner, Daniel; Lu, Xianguo; et al. (Physical review. D, Particles, fields, gravitation, and cosmology, 2013)
Correlations of two charged identical kaons (KchKch) are measured in pp collisions at √s=7 TeV by the ALICE experiment at the Large Hadron Collider (LHC). One-dimensional KchKch correlation functions are constructed in three multiplicity and four transverse momentum ranges. The KchKch femtoscopic source parameters R and λ are extracted. The KchKch correlations show a slight increase of femtoscopic radii with increasing multiplicity and a slight decrease of radii with increasing transverse momentum. These trends are similar to the ones observed for ππ and K0sK0s correlations in pp and heavy-ion collisions. However at high multiplicities, there is an indication that the one-dimensional correlation radii for charged kaons are larger than those for pions in contrast to what was observed in heavy-ion collisions at the Relativistic Heavy-Ion Collider.
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
The ALICE collaboration: B. Abelev, V. Angelov, O. Busch, M. Fasel, P. Glässel, R. Grajcarek, N. Herrmann, J. Klein, T. Krawutschke, M.J. Kweon, D. Lohner, X.-G. Lu, A. Maire, J. Mercado-Pérez, K. Oyama, Y. Pachmayer, K. Reygers, R. Schicker, J. Stachel, J.H. Stiller, J. Ulrich, S. Vallero, Y. Wang, B. Windelband, A. Zimmermann und weitere 949
Gesehen am 30.04.2021